The Internet and jobs: a giant opportunity for Europe - Echikson, William (Brussels, 2017)
"Over the past two decades, digitalisation has unleashed deep-seated fear among workers for the future of their jobs. Many of our daily activities, from entertainment to shopping, are being transformed. Uber drivers replace taxi drivers, artificial intelligence programmed legal review software replaces lawyers, and robots replace blue-collar manufacturing workers. Some studies predict that digitalisation and robotisation will cause job losses up to 50% of all jobs over the next few decades.